Why Christianity Happened: A Sociohistorical Account of Christian Origins (26–50 CE). By James G. Crossley - Rowland, Christopher (The journal of theological studies, 2008)
James Crossley offers an account of Christian origins which deliberately downplays the importance of the history of ideas, gives greater weight to socio-economic factors, and sets out to explain how it is that a Jewish, law-observant, movement in the eastern Mediterranean became a cosmopolitan religion. Early Christianity's particular kind of inclusiveness served a particular social need at this historical juncture and paved the way for the expansion of the movement outside the confines of Judaism, both socially and ideologically.